2022
DOI: 10.1038/s41598-022-05435-0
|View full text |Cite
|
Sign up to set email alerts
|

Colistin exposure enhances expression of eptB in colistin-resistant Escherichia coli co-harboring mcr-1

Abstract: Colistin resistance has increased due to the increasing and inappropriate use of this antibiotic. The mechanism involves modification of lipid A with phosphoethanolamine (PEtN) and/or 4-amino-4deoxy-l-arabinose (L-Ara4N). EptA and eptB catalyze the transfer of phosphoethanolamine to lipid A. In this study, gene network was constructed to find the associated genes related to colistin resistance, and further in vitro validation by transcriptional analysis was performed. In silico studies showed that eptB gene is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Most of the studies reported from India have not delved deeply into the mechanistic details of the Col R phenotype. Nevertheless, deleterious mutation in phoP , phoQ , pmrA , pmrB , and mgrB genes [12,13], complete deletion of mgrB [46], presence of efflux pump AcrAB and spermidine export protein MdtI/KpnF and mcr-1 [47] in K. pneumoniae ; the presence of mcr-1 in E. coli [48]; mutations at novel sites in pmrA , pmrB , lpxA , lpxD genes in A. baumannii [49] were reported to be involved in the development of Col R in India. Therefore, more investigations are warranted to understand the molecular details of the reasons behind ColR development.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies reported from India have not delved deeply into the mechanistic details of the Col R phenotype. Nevertheless, deleterious mutation in phoP , phoQ , pmrA , pmrB , and mgrB genes [12,13], complete deletion of mgrB [46], presence of efflux pump AcrAB and spermidine export protein MdtI/KpnF and mcr-1 [47] in K. pneumoniae ; the presence of mcr-1 in E. coli [48]; mutations at novel sites in pmrA , pmrB , lpxA , lpxD genes in A. baumannii [49] were reported to be involved in the development of Col R in India. Therefore, more investigations are warranted to understand the molecular details of the reasons behind ColR development.…”
Section: Discussionmentioning
confidence: 99%
“…eptA catalyzes the transfer of PEtN from phosphatidylethanolamine onto the lipid A of LPS and eptB catalyzes the addition of a PEtN moiety to the outer 3-deoxy-d-manno-octulosonic acid (Kdo) residue of a Kdo(2)-lipid A. Presence of mcr - 1 supplements the activity of eptB gene in higher transcriptional expression when the E. coli exposed to a sub-inhibitory concentration of colistin ( Elizabeth et al., 2022 ).…”
Section: Co-factors and Co-selectionmentioning
confidence: 99%
“…This modification increases the charge on LPS (the initial target of the polymyxins), which decreases polymyxin binding and leads to resistance [ 21 ]. A recent study revealed that colistin exposure enhances the expression of eptB in colistin-resistant E. coli coharboring mcr -1 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%